1994
DOI: 10.1083/jcb.127.6.2061
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin and APC compete for the interaction with beta-catenin and the cytoskeleton.

Abstract: Abstract. &Catenin is involved in the formation of adherens junctions of mammalian epithelia. It interacts with the cell adhesion molecule E-cadherin and also with the tumor suppressor gene product APC, and the Drosophila homologue of B-catenin, armadillo, mediates morphogenetic signals. We demonstrate here that E-cadherin and APC directly compete for binding to the internal, armadillo-like repeats of/5-catenin; the NH2-terminal domain of/3-catenin mediates the interaction of the alternative E-cadherin and APC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
379
1
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 593 publications
(391 citation statements)
references
References 54 publications
8
379
1
3
Order By: Relevance
“…The core of the pathway is the stability of b-catenin, a protein that plays a dual role in intercellular junction formation and transcriptional regulation (Hulsken et al 1994;Behrens et al 1996;Nelson and Nusse 2004). Indeed, b-catenin was first characterized as an adherens junction protein, which, through its Armadillo repeats, binds to the core transmembrane adhesion protein Ecadherin and, through its N-terminal domain, associates with a-catenin, a protein that binds actin and other actinregulators.…”
Section: Overview Of Wnt Signaling Pathwaysmentioning
confidence: 99%
“…The core of the pathway is the stability of b-catenin, a protein that plays a dual role in intercellular junction formation and transcriptional regulation (Hulsken et al 1994;Behrens et al 1996;Nelson and Nusse 2004). Indeed, b-catenin was first characterized as an adherens junction protein, which, through its Armadillo repeats, binds to the core transmembrane adhesion protein Ecadherin and, through its N-terminal domain, associates with a-catenin, a protein that binds actin and other actinregulators.…”
Section: Overview Of Wnt Signaling Pathwaysmentioning
confidence: 99%
“…Early studies identified E-cadherin/catenin interactions as imperative for cell -cell adhesion (Chitaev and Troyanovsky, 1998). b-Catenin binds with high affinity to the carboxyl-terminal region of the cadherin cytoplasmic tail, while a-catenin serves as an anchor, by bridging to aactinin, to link the complex to the actin cytoskeleton (Aberle et al, 1994;Hulsken et al, 1994;Funayama et al, 1995;Jou et al, 1995;Rimm et al, 1995). These molecules not only play structural roles but also alter cell responses and phenotypes.…”
mentioning
confidence: 99%
“…These molecules not only play structural roles but also alter cell responses and phenotypes. b-Catenin is also found to immunoprecipitate with the APC tumour suppressor protein (Su et al, 1993;Hulsken et al, 1994;Shibata et al, 1994), and has been recently identified as an oncogene (Kim et al, 2002;Minamoto et al, 2002;Kielhorn et al, 2003;Schneider et al, 2003). It is also central to cell signalling, as upon dissociation from E-cadherin, it transits to the nucleus to alter transcriptional profiles (Mason et al, 2002;van de Wetering et al, 2002).…”
mentioning
confidence: 99%
“…9,10 Normal cells have little free ␤-catenin proteins, and most of them are bound to cadherin. The rest form the complex with APC (adenomatous polyposis coli) gene products and glycogen synthetase kinase-3␤ (GSK-3␤).…”
mentioning
confidence: 99%